Bioactive compounds in microalgae and their potential health benefits. (October 2022) - Zhou, Linhui; Li, Kunning; Duan, Xinyu; Hill, David; Barrow, Colin; Dunshea, Frank; Martin, Gregory; Suleria, Hafiz
Abstract: Driven by increasing food security concerns, microalgae have drawn attention due to their resource-efficient production and high nutritional value. Microalgae are highly diverse and contain significant amounts of various bioactive compounds, including bioactive peptides, PUFA, vitamins, phenolics, carotenoids, sterols, and so on. These bioactive compounds can exhibit considerable health promoting effects, such as antioxidant, anti-inflammatory, anti-cancer, and antimicrobial effects. In parallel, research into bioavailability is being conducted to support and guide the application of these compounds. Currently, the application has been targeted in the food and aquaculture industries, with the pharmaceutical, cosmetic, and biofuels industries looking to apply more microalgae ingredients as well. However, there are still obstacles to the commercial application of microalgae due to the immaturity of the technology and high production costs. This review provides an overview of information on the composition as well as the distribution of active substances in microalgae, highlighting the main active substance digestion pathways and the corresponding factors influencing bioavailability, describing the mechanisms by which microalgal bioactive compounds exert a variety of health effects, and the development of commercial applications in different industries, providing guidance for the development of their potential applications and wider consumption. Highlights: Systematically reviewed bioactive compounds and compositions in microalgae. Summarizing and comparing the bioavailability of different compounds in microalgae. Microcapsules and liposomes can improve the utilization of microalgae. Microalgal components exert nutritional properties through different mechanisms.